2019
DOI: 10.1038/s41597-019-0234-z
|View full text |Cite
|
Sign up to set email alerts
|

An updated and unified earthquake catalog from 1787 to 2018 for seismic hazard assessment studies in Mexico

Abstract: Here we present a new updated and unified Poissonian earthquake catalog for Mexico. The details about the catalog compilation, the removal of duplicate events, unifying the magnitude scales, removal of dependent events through the declustering process and its completeness analysis are presented. Earthquake and focal mechanism data have been compiled from various local, regional and international sources. Large earthquake events (MW ≥ 6.5) have been carefully revised for their epicentral locations and magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 92 publications
2
25
0
Order By: Relevance
“…In this work, the method suggested by Gardner and Knopoff [78] was selected due to its clarity, simplicity, and stability [2,3,32]. Besides, this method has proven its efficiency in most of the recent research [8,10,31,81,82], and particularly for the studied area [2,7]. As the more energetic an earthquake is, the more temporal and geographical extension is involved, this method defines temporal and spatial windows depending on the main earthquake.…”
Section: Declusteringmentioning
confidence: 99%
See 4 more Smart Citations
“…In this work, the method suggested by Gardner and Knopoff [78] was selected due to its clarity, simplicity, and stability [2,3,32]. Besides, this method has proven its efficiency in most of the recent research [8,10,31,81,82], and particularly for the studied area [2,7]. As the more energetic an earthquake is, the more temporal and geographical extension is involved, this method defines temporal and spatial windows depending on the main earthquake.…”
Section: Declusteringmentioning
confidence: 99%
“…In seismicity studies, some parameters have a particularly important role. Among others, these are the maximum magnitude (recorded, possible, expected), the b-value of the Gutenberg-Richter (GR) frequency-magnitude (FMD) relation, and a parameter related to the seismic activity (mean seismic activity rate or the a-value of GR) [1][2][3][4][5][6][7][8][9][10][11][12][13]. Some of these studies are based on seismic zonations [1,2], and others are found in a purely geographical grid division [7,11,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations